Parents' experiences in dealing with the development of adolescent Autistic Sexuality in West Java Province: A Phenomenological Study - Anni Sinaga; Achmad Hufad; Endang Rochyadi; Imas Diana Aprilia (Eduvest - Journal of Universal Studies, 2024)
Families who have autistic children may experience a burden in their lives. Little is known about how parents deal with their autistic children who are entering adolescence and are experiencing sexual development. What parents do to deal with the development of adolescent autistic sexuality can be found in qualitative research. The participants are parents with children who are autistic. The researcher contacted the parents and explained the informed consent; if parents agreed, they would sign the informed consent and then decide to place a time to interview the participant with the researcher, interviews with participants from January 2023-March 2023. This study aims to explore family experiences in dealing with sexuality development in adolescents with autism spectrum disorders. This phenomenological study collected data through in-depth interviews with semi-structured open-ended questions of seven child participants with autism spectrum disorders. Eleven themes constructed from this study are shy children when reminded not to hold their genitals, children are distracted when holding their genitals, children going through menstruation, children showing sexual behaviour by opening their pants, children holding their genitals, children hugging their mothers and seek attention, children stimulate themselves and others, children are easily aroused, children cannot distinguish boys and girls children like to clamp their genitals, And the child likes the prone position on the floor. Parents who feel that their child is currently facing the developmental phase of adolescent sexuality independently. They recommend that Parents provide adequate support, including appropriate education and open dialogue about the changes their child is experiencing.